PECULIARITIES OF PSYCHOLOGICAL WELL-BEING OF STUDENTS WITH DIFFERENT ETHNIC OWNERSHIP INCLUDED IN A UNIFORM EDUCATIONAL ENVIRONMENT OF THE UNIVERSITY - Tikhomirova, E.V.; Vishnevskaya, O.N.; Morozova, D. N. (Արդի հոգեբանություն, 2022)
The article is devoted to the study of the peculiarities of psychological well-being and the specifics of understanding its indicators, barriers and resources among students of different ethnicity, included in the unified educational environment of the university. The first part of the study involved 300 students (M = 19.64; SD = 2.61) and were interviewed about the semantics they put into their own psychological well-being, its indicators and barriers to achievement. The second part - 60 students: 30 Russian and 30 representatives of other ethnic groups, representatives of Asian culture. As a result, the authors came to the conclusion that along with general trends in understanding and experiencing psychological well-being among students of different ethno cultural groups who are in a single educational environment, there are also specific trends related to the mentality, culture, customs and the very specifics of the social situation of educational migration. Basically, students are moderately satisfied with their own lives, as they see a number of barriers that prevent them from fully feeling the state of psychological well-being.